2005
DOI: 10.1007/s10227-005-0105-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and Growth Factor mRNA Expression Patterns Associated with the Hypercontracted, Hyperpigmented Healing Phenotype of Red Duroc Pigs: A Model of Abnormal Human Scar Development?

Abstract: The molecular expression pattern observed correlates well with the gross healing phenotype and matrix molecule expression patterns previously reported in red Duroc pigs. These findings enhance our understanding of the processes associated with fibroproliferative scar-formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 59 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…However, expression of types I and III collagen, heat shock protein 47, bone morphogenic protein 1, diverse proteoglycans, and osteopontin differed in pattern, with the red Duroc pig exhibiting a unique biphasic pattern, undocumented previously [30]. Subsequent studies by the same group using electric dermatome wounds on the backs of red Duroc pigs revealed characteristics in expression of cytokines, transcription factors, growth factors, and receptors similar to human scars [31]. Stewart et al, also from this group, reported in 2006 that the kinetics of blood flow in the red Duroc model were comparable with the previously observed laser Doppler imaging of human skin wounds and hypertrophic scars [32].…”
Section: Experimental Models Of Abnormal Scarringmentioning
confidence: 99%
“…However, expression of types I and III collagen, heat shock protein 47, bone morphogenic protein 1, diverse proteoglycans, and osteopontin differed in pattern, with the red Duroc pig exhibiting a unique biphasic pattern, undocumented previously [30]. Subsequent studies by the same group using electric dermatome wounds on the backs of red Duroc pigs revealed characteristics in expression of cytokines, transcription factors, growth factors, and receptors similar to human scars [31]. Stewart et al, also from this group, reported in 2006 that the kinetics of blood flow in the red Duroc model were comparable with the previously observed laser Doppler imaging of human skin wounds and hypertrophic scars [32].…”
Section: Experimental Models Of Abnormal Scarringmentioning
confidence: 99%
“…Recent studies have focused on abnormal inflammatory responses associated with skin wound healing in a pig model [ 11 13 ] and inflammatory responses associated with joint injuries leading to joint contractures in both humans [ 14 , 15 ] and rabbits [ 16 , 17 ]. In both the pig and rabbit models, a response to tissue injury leads to a hypertrophic-like healing response in the red Duroc pig model [ 11 13 ] and joint contractures in the rabbit model [ 16 , 17 ]. In the pig model, a unique “biphasic” inflammatory process was detected after skin injury, while in the rabbit model it appeared that the initial injuries to the joint capsule and bone led to a chronic inflammatory phenotype accompanied by a fibrotic thickening of the capsule.…”
Section: Introductionmentioning
confidence: 99%
“…It includes 1) a validated large animal, Duroc (pigmented, red, fibroproliferative)/Yorkshire (non-pigmented, white, non-fibroproliferative) porcine in vivo model of cutaneous fibroproliferation that enables the study of two significant variables simultaneously over time, wound depth and skin pigmentation, making it unique among fibrosis models [27], [28], [29], [30], [31], [32], [33], [34] (confirmed by Hart [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46]), 2) laser capture microdissection that enables the study of the microanatomical locations of skin, thus avoiding homogenization of the entire organ, and 3) annotation of the Affymetrix Porcine GeneChip® enabling global profiling.…”
Section: Introductionmentioning
confidence: 98%